The antigen binding domain of non-idiotypic human anti-F(ab')2 autoantibodies: study of their interaction with IgG hinge region epitopes - Welschof, Martin; Reineke, U.; Kleist, Christian; Kipriyanov, S.; Little, M.; Volkmer-Engert, R.; Schneider-Mergener, J.; Opelz, Gerhard; Terness, Peter (Human immunology, 1999)
In previous studies we described a natural human IgG-anti-F(ab')2 autoantibody family with immunoregulatory properties. Genes coding for the variable regions of the heavy and light chains of the Abs were isolated from a natural Ig gene library and scFv Abs were expressed in E. coli. The scFv Abs bound to F(ab')2 but not to Fab fragments. This points to an epitope located in the hinge region since Fab fragments are lacking most of the hinge. In order to verify our hypothesis, double chain peptides comprising the lower-, middle-, and part of the upper hinge subregion of IgG1-IgG4 were synthesized on cellulose membranes and tested for binding to the Abs. The results show binding of Abs to IgG1 and IgG4 hinge region peptides. In order to identify the key residues of the discontinuous epitopes we carried out complete substitutional analyses in which each amino acid of the wt peptides was substituted by all other amino acids except cysteine. The exchange of proline in the IgG1 or IgG4 middle hinge region abrogated the binding, revealing the importance of this subregion for epitope expression. No binding to the IgG2 or IgG3 hinge was detected. These results indicate that scFv anti-F(ab')2 Abs recognize the hinge region of IgG1 and IgG4 and that the expression of the epitope depends on an intact middle hinge subregion.
Gesehen am 19.02.2021